Środowiskowe Centrum Zdrowia Psychicznego a zadania zdrowia publicznego = Community Mental Health Center in the context of public health care - Furtak-Niczyporuk, Marzena; Filipek, Mariusz (Journal of Education, Health and Sport, 2017)
Furtak-Niczyporuk Marzena, Filipek Mariusz. Środowiskowe Centrum Zdrowia Psychicznego a zadania zdrowia publicznego = Community Mental Health Center in the context of public health care. Journal of Education, Health and Sport. 2016;6(11):430-443. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.174604 http://ojs.ukw.edu.pl/index.php/johs/article/view/4018 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 27.11.2016. Środowiskowe Centrum Zdrowia Psychicznego a zadania zdrowia publicznego Community Mental Health Center in the context of public health care Marzena Furtak-Niczyporuk, Mariusz Filipek *Katedra i Zakład Zdrowia Publicznego Uniwersytet Medyczny w Lublinie Adres do korespondencji: Katedra i Zakład Zdrowia Publicznego Uniwersytet Medyczny w Lublinie Lublin 20-093, ul. Chodźki 1 Dr n. med. Marzena Furtak–Niczyporuk Mecenas Mariusz Filipek *Katedra i Zakład Zdrowia Publicznego Uniwersytet Medyczny w Lublinie Streszczenie Wstęp. Wzrastająca liczba osób dotkniętych zaburzeniami psychicznymi, zarówno na świecie, jak i w kraju, karze zwrócić społeczną uwagę na upowszechnienie środowiskowej opieki psychiatrycznej. Powołanie Środowiskowego Centrum Zdrowia Psychicznego mogłoby dostarczyć wszystkich medycznych świadczeń psychiatrycznych w połączeniu z usługami pomocy społecznej na poziomie jednostki samorządu terytorialnego szczebla powiatu. Cel. Celem pracy była ocena i propozycja sposobu realizacji zadań zdrowia publicznego przez Środowiskowe Centra Zdrowia Psychicznego w Polsce. Zgodnie z założeniami Narodowego Programu Ochrony Zdrowia Psychicznego Centrum byłoby zlokalizowane na poziomie jednostki samorządu terytorialnego szczebla powiatu. Dlatego przeprowadzono badania jednostek samorządu terytorialnego, aby zobrazować obecnie podejmowane przez nich działania na rzecz promocji zdrowia psychicznego oraz wsparcia osób z zaburzeniami psychicznymi, a które to samorządy będą wspierały Środowiskowe Centra Zdrowia Psychicznego. Materiał i metoda. Badania pracowników powiatowych oraz gminnych jednostek samorządu terytorialnego z obszaru województwa lubelskiego w zakresie postępowania z osobami chorymi psychicznie oraz rozwoju środowiskowej opieki psychiatrycznej dokonano na podstawie kwestionariusza ankiety składającego się z 29 pytań. Druga część badań aktów prawnych pozwoliła na przygotowanie rekomendacji efektywnego realizowania zadań zdrowia publicznego w Środowiskowych Centrach Zdrowia Psychicznego. Wyniki. Pomoc oferowana osobom dotkniętym zaburzeniami psychicznymi przez jednostki samorządu terytorialnego w większości sprowadza się do wypłacania zasiłków – 71% badanych. Blisko połowa badanych nie posiada wiedzy o sposobach zapobiegania zaburzeniem psychicznych – 47% badanych. Aż 80% badanych nie zna programu zdrowia psychicznego dla jednostki w której pracuje, co oznacza brak takich programów, choć są dla samorządów obowiązkowe, bądź też ich istnienie wyłącznie na papierze. Realizacja zadań zdrowia publicznego wymaga ich uszczegółowienia w obszarze monitorowania stanu zdrowia społeczeństwa, edukacji na różnych poziomach oraz współpracy międzysektorowej. Wnioski. Potrzeba wprowadzenia sprawnych i skutecznych działań, które przyczynią się do upowszechnienia środowiskowej opieki psychiatrycznej. Niewątpliwie potrzeba określenia precyzyjnych zadań i źródeł ich finansowania do efektywnych działań pomocy osobom dotkniętym zaburzeniami psychicznymi w ich środowisku lokalnym. Tu właśnie dużą rolę pełnią jednostki samorządu terytorialnego poprzez działalność podległych sobie gminnych/miejskich/powiatowych ośrodków pomocy społecznej i innych jednostek organizacyjnych wykonujących zadania ochrony zdrowia psychicznego. Z pewnością realizacja zadań z zakresu zdrowia publicznego, za którą także odpowiadają jednostki samorządu terytorialnego wymaga ich uszczegółowienia. Zaproponowane rozwiązania realizacji zadań publicznych dają szansę na ograniczenie lub wyeliminowanie wieli chorób, w tym zaburzeń psychicznych. Szczególnie realizacja zadań zdrowie publicznego przez Środowiskowe Centra Zdrowia Psychicznego przyczyni się do szybszego zdrowienia osób dotkniętych zaburzeniami psychicznymi, a też wyeliminowania ich marginalizacji i wykluczenia społecznego. Słowa kluczowe: jednostki samorządu terytorialnego, środowiskowa opieka psychiatryczna Abstract Introduction. An increasing number of people affected by mental disorders, both worldwide and countrywide, draws public attention to providing community mental health care. The establishment of the Community Mental Health Center could provide all psychiatric services and social assistance within the area of local government units. Object. The object of the study was to evaluate and suggest the most effective way of performing public health duties by Community Mental Health Centers in Poland. According to the National Mental Health Prevention Program the CMHC would be located within the powiats. Therefore, local government units were the object of the study in order to present actions undertaken towards the promotion of mental health and to support people affected by mental disorders, which units will be bound to support the Community Mental Health Center. Materials and methods. The study of local government units employees, both gminas and powiats, within the area of Lublin Voivodeship, in terms of assistance provided to people affected by mental disorders and the development of community mental health care, was conducted by means of a questionnaire consisting of 29 questions. The second part of the study conducted in terms of the legislation allowed the preparation of recommendations for an effective performance of public health duties by the Community Mental Health Centers. Results. The majority of support provided to people affected by mental disorders offered by local government units comes in the form of the payment of benefits – 71% of respondents. Nearly half of the respondents have no knowledge of how to prevent mental disorder – 47% of respondents. As many as 80% of respondents do not have any knowledge about the mental health program dedicated to the unit they work in, which means the lack of such programs although local governments are in the need of it, or the existence thereof only on paper. Performance of public health duties requires its detailed description in terms of public health monitoring, the overall education and intersectoral cooperation. Conclusions. The need for both efficient and effective performance contributing to the promotion of community mental health care. Undoubtedly, the need to precisely determine the tasks and funding of the most effective actions for providing help to people affected by mental disorders in their local environment. Local government units are the main character of the aforementioned actions through the activity of subordinate communal/municipal/county social assistance centers and other units performing tasks onsidering mental health care. It is certain that the performance of tasks in terms of public health that local government units are responsible for, needs to be precisely determined. Solutions suggested herein provide an opportunity to reduce or even eliminate many diseases, including mental disorders. Especially the performance of public health care provided by the Community Mental Health Centers will contribute to the quicker recovery of people affected by mental health problems and also eliminate the marginalization and social exclusion of the aforementioned. Key words: local government unit, community mental health services